AN ANALYSIS OF PLOT IN FILM THE THEORY OF EVERYTHING BY JAMES MARSH - Sholihah, Farkhatus (Universitas Islam Lamongan, 2021)
Plot is one of the important elements contained in narrative literary works. Plots in literary works, films, stories, or other narratives are sequences of several events, and each of these events influences subsequent events. Now, the film is considered as a powerful communication medium for the masses that are being targeted, because of its audio-visual nature, that is, vivid images and sounds. With pictures and sound, movies can tell a lot in a short time. This study Â focuses on the analysis of how the plot is used in the film The Theory of Everything. Thus, the aim is to describe the plot in the film The Theory of Everything.This research used a descriptive qualitative method. First, the writer categorizes several fragments of a sentence, dialogue, and scene. Next, look for, analysis, and interpret it to obtain the plot structure in accordance with the theory. From the results of the analysis obtained the answer that the film is told in its entirety starting from exposition, rising action, climax, and falling action. And the film closes with a closed ending. So the film goes forward or progressive plot. The authors hope that the results of this study will benefit future researchers who are interested in the work of literature in the form of films, especially in the plot.Â Keywords: Film, plotÂ